An Introduction to Contemporary Hadith Science: A Critical Study of the Book Al-Wasīṭ fī ‘Ulūm Wa Muṣṭalaḥ Al-Ḥadīṡ - Kholis, Nur (Universitas Ahmad Dahlan, 2023)
This paper discusses one of the contemporary hadith science books entitled al-Wasīṭ fī 'Ulūm wa Muṣṭalah al-Ḥadīṡ authored by Abu Syuhbah. There are at least several reasons that form the basis of the relevance of this study. First, in general, studies of ‘Ulūm al-Ḥādīṡ books are now rarely found, especially in Indonesia. Research is now more aimed at a figure's thoughts, independently or comparatively. If this is not the case, then the research is more aimed at thematic studies. It is scarce to find discussions of ‘Ulūm al-Ḥādīṡ books independently. Secondly, this book is unique to be studied. Among other things, (1) this book, by Abu Syuhbah in his introduction, is intended not only for those who are deeply engaged in the field of hadith but also for Muslims in general. (2) The book does not follow the organization of the previous books of hadith science. For example, in the previous books, the discussion would start from the definition of saḥīḥ, ḥasan and ḍa‘īf traditions. In contrast, al-Wasith discusses some technical terms related to hadith science. (3) It also discusses the development of terms that differ from their original meanings in the previous books. Therefore, this review aims to show the